New and old concrete interface binder and preparation method thereof
By using nano calcium silicate and temperature controlled release coagulant microcapsules in the interface adhesive, combined with the thermal conducting agent, the problems of short operating window period, unstable bond strength and insufficient anti-seepage performance of the existing interface adhesive are solved, and higher bond strength and anti-seepage performance are achieved, and the operating window period is extended.
Patent Information
- Application Number
- CN202411870918.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The operating window period of existing interface adhesives is short, the bonding strength is unstable, and the impermeability resistance is insufficient, resulting in poor construction quality and reduced structural service life.
Nano calcium silicate is used as the gelling agent, and through the combination of temperature controlled release coagulant microcapsules and thermal conducting agent, the operation window period is extended, and the bond strength and anti-seepage performance are improved.
The operating window period of the interface adhesives of new and old concrete has been extended, the bonding strength and impermeability are improved, and the durability and stability of construction joints are enhanced.
Smart Images

Figure BDA0005195740180000011 
Figure BDA0005195740180000031 
Figure BDA0005195740180000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of interface adhesives, and in particular relates to an adhesive for the interface between new and old concrete and a preparation method thereof. Background Art
[0002] In the construction of large underground projects, due to the requirements of construction technology and project progress, it is often necessary to pour concrete in sections, which creates construction joints. The existence of construction joints is crucial to ensure the integrity and durability of the project. Proper treatment of construction joints can effectively prevent the intrusion of moisture, gas and other harmful substances, and ensure the strength and stability of the structure. As an important material, interface adhesives are widely used to strengthen the connection between new and old concrete at the construction joint.
[0003] At present, the existing interface adhesives usually use cement-based penetrating crystalline waterproof materials or interface treatment agents, which have the following problems: 1) Due to the long interval between the construction of new and old concrete at the construction joint, a series of operations such as tying steel bars and supporting formwork are required after applying the interface agent. The operation window period of the interface adhesives currently on the market is relatively short, and it is often impossible to complete the new concrete construction within the operation window period of the interface adhesive, thereby affecting the quality of the project; 2) The bonding strength of the interface adhesives currently on the market is unstable and cannot provide a durable and reliable concrete connection, thereby increasing the risk of the structure; 3) The anti-seepage performance is not satisfactory and cannot effectively prevent water penetration, thereby causing environmental damage and reducing the service life of the structure.
[0004] Therefore, it is of great significance to develop a new-old concrete interface adhesive and a preparation method with a long operating window, high bonding strength, good bonding stability, and excellent anti-seepage performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects in the prior art and provide a new-old concrete interface adhesive and a preparation method thereof, which has a long operating window period, high bonding strength, good bonding stability and excellent anti-seepage performance.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A new-old concrete interface adhesive comprises the following raw materials in parts by weight:
[0008]
[0009] The temperature-controlled-release coagulant microcapsules are core-wall structure coagulants made by embedding coagulants in wall materials; when the temperature is greater than or equal to 40 degrees Celsius, the wall layer of the core-wall structure coagulant dissolves to release the core layer coagulant.
[0010] As a further technical solution, the wall material includes one or more of gelatin, gum arabic, xanthan gum, polyvinyl alcohol, and polyacrylic acid;
[0011] As a further technical solution, the coagulant includes one or more of aluminum sulfate, alcohol amine, and calcium salt;
[0012] As a further technical solution, the alcoholamine includes one or more of diethanolamine and triethanolamine;
[0013] As a further technical solution, the calcium salt includes one or more of calcium formate and calcium acetate.
[0014] As a further technical solution, the coagulant includes 3-6 parts by weight of aluminum sulfate, 3-6 parts by weight of alcoholamine and 1-3 parts by weight of calcium salt.
[0015] As a further technical solution, the amount of the wall material is 20-40% of the weight of the coagulant;
[0016] As a further technical solution, a method for preparing temperature-controlled release coagulant microcapsules comprises the following steps:
[0017] Add the wall material into the solvent and stir at 40-80 degrees Celsius until dissolved to prepare a wall material solution;
[0018] The coagulant is added into the wall material solution, stirred evenly, and then spray-dried or concentrated and evaporated to dryness to obtain temperature-controlled release coagulant microcapsules.
[0019] As a further technical solution, the solvent is water.
[0020] As a further technical solution, the gelling agent includes one or more of nano calcium silicate, calcium sulfate whiskers, sodium sulfate, and nano silicon dioxide;
[0021] As a further technical solution, the film-forming agent includes one or more of redispersible polymer rubber powder, elastic emulsion, and styrene-acrylic emulsion;
[0022] As a further technical solution, the crack inhibitor includes one or more of a nano-scale crack inhibitor and other crack inhibitors;
[0023] As a further technical solution, the nano-scale crack inhibitor includes one or more of nano-plant fibers and nano-cellulose;
[0024] As a further technical solution, the other crack inhibitor includes carbon fiber;
[0025] As a further technical solution, the nanocellulose includes pure nanocellulose or modified nanocellulose;
[0026] As a further technical solution, the thermal conductor is one or more of alumina, nano carbon black and graphite.
[0027] As a further technical solution, the gelling agent includes 30-40 parts by weight of nano calcium silicate, 5-10 parts by weight of calcium sulfate whiskers, 1-5 parts by weight of sodium sulfate, and 1-10 parts by weight of nano silicon dioxide.
[0028] As a further technical solution, it also includes 0.05-0.1 parts by weight of a water reducing agent and / or 0.2-0.5 parts by weight of other additives;
[0029] As a further technical solution, the other auxiliary agents include water reducing agent, anti-seepage agent, suspending agent, thickening agent, defoaming agent and preservative.
[0030] As a further technical solution, the water reducer includes one or more of a polycarboxylate water reducer or a naphthalene water reducer;
[0031] As a further technical solution, the anti-seepage agent includes one or more of an organic silicon hydrophobic agent, sodium methyl siliconate, sodium ethyl siliconate, or polyethyl hydroxysiloxane;
[0032] As a further technical solution, the suspending agent includes an anionic surfactant or a nonionic surfactant;
[0033] As a further technical solution, the thickener includes one or more of polyvinyl alcohol or sodium polyacrylate;
[0034] As a further technical solution, the defoaming agent includes one or more of a polyether defoaming agent and a silicone oil defoaming agent;
[0035] As a further technical solution, the preservative includes benzoate.
[0036] As a further technical solution, the new-old concrete interface adhesive comprises the following raw materials in parts by weight:
[0037]
[0038] The coagulant is added in the form of temperature-controlled release coagulant microcapsules.
[0039] As a further technical solution, the new-old concrete interface binder further comprises water, and the amount of water used is 40-60% of the total weight of the powder material in the new-old concrete interface binder.
[0040] The preparation method of the new-old concrete interface adhesive comprises the following steps:
[0041] Step 1, weighing each raw material in proportion, adding a water reducer into water, stirring and dissolving, adding the nano-silicon dioxide and nano-scale crack inhibitor in the gelling agent, stirring and dispersing and ultrasonically dispersing in turn to obtain a nano-material solution;
[0042] Step 2: Mix the temperature-controlled release coagulant microcapsules and other materials in the gelling agent, stir and disperse them evenly, then add the film-forming agent, thermal conductive agent, other crack inhibitors and other additives, and continue stirring until they are evenly dispersed to obtain powder material A;
[0043] Step 3: Slowly add the nano material solution into the powder material A and stir until it is evenly dispersed to obtain the new and old concrete interface adhesive.
[0044] In the present invention,
[0045] 1) Gelling agent
[0046] Nano-calcium silicate reacts with water to form hydrated calcium silicate gel, and the SO4 provided by calcium sulfate whiskers and sodium sulfate 2- It reacts with the unreacted calcium hydroxide and monosulfur calcium sulfoaluminate hydrate in the old concrete interface to form needle-shaped calcium sulfonate. Nano-silica can react with the excess calcium hydroxide in the old concrete interface to form calcium silicate hydrate gel. Multiple gelling components make the adhesive form a dense hydration product at the interface of the old concrete. Nano-particles are smaller in size than traditional silicate cement or ultra-fine silicate cement. Nano-clinker can penetrate into the pores of the old concrete interface, react directly in the pores to fill the pores, and make the adhesive firmly bonded to the old concrete interface.
[0047] 2) Coagulant
[0048] The coagulant of the present invention is prepared into microcapsules from wall materials. When new concrete is poured, the hydration heat generated by the hydration reaction of the new concrete causes the microcapsule shell to dissolve and release the coagulant components, thereby promoting the hydration reaction of the new concrete at the interface and improving the reaction strength of the new concrete and the adhesive, thereby firmly bonding the new concrete to the old concrete.
[0049] 3) Film-forming agent
[0050] After the present invention is applied to the old concrete base surface, the film-forming agent can penetrate into the pores of the old concrete, and the polymer film is interlaced with the hydration products generated by the hydration of the gelling component after the polymer film is formed; at the same time, the gelling agent is hydrated on the interface surface, and the hydrated calcium silicate gel and calcium aluminate generated by the hydration are in the form of fibers and needles, which grow crosswise with the polymer film at the interface. The expansion of the seam at the interface is limited by the synergistic effect of the two components, thereby enhancing the bonding effect of the construction joint interface.
[0051] 4) Crack inhibitor
[0052] The addition of crack inhibitors can act as a bridge to transfer loads across cracks, making the stress field in the concrete more continuous and uniform, thereby weakening and eliminating the further expansion of cracks at construction joints.
[0053] 5) Thermal Conductive Agent
[0054] The present invention adds a heat conductor to transfer the hydration heat generated by the hydration reaction in the newly poured concrete to the interface between the new and old concrete, thereby promoting the thermal dissolution of the microcapsule shell and releasing the accelerating coagulation component.
[0055] 6) Water reducing agent
[0056] Water reducer can help nanoparticles disperse evenly, increase the fluidity of adhesives, and maintain the workability of adhesives.
[0057] 7) Other additives
[0058] The present invention also improves its performance by adding an anti-seepage agent, a suspending agent, a thickener, a defoaming agent, a preservative, etc. For example, the anti-seepage agent can improve the interfacial anti-seepage property, the suspending agent can help the nanoparticles to be evenly dispersed and remain stable, the thickener can adjust the consistency of the binder, the defoaming agent can reduce the generation of foam in the system, and the preservative can increase the shelf life of the binder and extend its usable time.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] On the one hand, the present invention uses nano calcium silicate as a gelling agent to promote it to penetrate into the pores of the old concrete interface, thereby improving the firm bonding between the adhesive and the old concrete interface. On the other hand, the coagulant is wrapped with a temperature-controlled microcapsule, and by adding a heat conductor, the hydration heat generated by the hydration reaction in the newly poured concrete is transferred to the interface between the new and old concretes, so that the temperature-controlled microcapsules are dissolved by heat, the coagulant is released, and the bonding effect between the adhesive and the newly poured concrete is provided, thereby extending the operating window period of the adhesive at the interface between the new and old concretes. In addition, the present invention also greatly improves the bonding, impermeability and durability of the construction joints of the new and old concretes by controlling the selection and dosage of each raw material. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a schematic diagram of the construction structure when conducting the anti-seepage performance test in Effect Example 2;
[0062] exist Figure 1 Among them, 1. Construction joint, 2. Grouting pipe, 3. External waterproof layer, 4. Cavity water storage baffle. DETAILED DESCRIPTION
[0063] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0065] In an embodiment of the present invention,
[0066] Nano calcium silicate (50nm): Jingjia Mineral Products Co., Ltd.
[0067] Redispersible polymer powder 5010: Wacker Chemie Co., Ltd.;
[0068] Sodium sulfate: analytical grade, Xilong Scientific Co., Ltd.;
[0069] Nanosilicon dioxide (20 nm): McLean Biochemical Technology Co., Ltd.;
[0070] Aluminum sulfate: analytical grade, Xilong Scientific Co., Ltd.;
[0071] Triethanolamine: analytical grade, Xilong Scientific Co., Ltd.;
[0072] Calcium acetate: analytical grade, Xilong Scientific Co., Ltd.;
[0073] Nanocellulose (1-100nm): CNF, diameter 5-20nm, length 100-500nm, Langfang Flashpoint Technology Co., Ltd.;
[0074] Nano carbon black BP2000: Cabot Corporation, USA;
[0075] Polycarboxylate water reducer 3301: Sika (China) Co., Ltd.;
[0076] Silicone hydrophobic agent SHP50: Dow Chemical Company;
[0077] Anionic surfactant (sodium dodecylbenzene sulfonate): analytical grade, Xilong Scientific Co., Ltd.;
[0078] Polyvinyl alcohol: analytical grade, Xilong Scientific Co., Ltd.;
[0079] Polyether defoamer: FS202, Nanjing Xinyi Synthetic Technology Co., Ltd.;
[0080] Benzoate: sodium benzoate, Xilong Scientific Co., Ltd.;
[0081] In the comparative example,
[0082] Calcium silicate (particle size 50 μm): Jingjia Mineral Products Co., Ltd.;
[0083] Silicon dioxide (10 μm): Shijiazhuang Leitai Technology Co., Ltd.;
[0084] Cellulose (particle size 55 μm): Jiangsu Longhao New Materials Co., Ltd.;
[0085] Unless otherwise specified, the raw materials used in the present invention are commercially available.
[0086] Example 1
[0087] A new-old concrete interface adhesive comprises the following raw materials in parts by weight:
[0088]
[0089] The coagulant is embedded in a wall material to form a temperature-controlled release coagulant microcapsule, and is added in the form of a temperature-controlled release coagulant microcapsule; the gelatin wall material of the controlled release coagulant microcapsule softens and dissolves above 40 degrees Celsius, thereby releasing the coagulant;
[0090] The preparation method thereof comprises the following steps:
[0091] Step 1, weigh each raw material by weight;
[0092] Step 2: Encapsulation of coagulant:
[0093] Adding the wall material gelatin into the solvent water, heating to 65 degrees Celsius, stirring to dissolve, and preparing the wall material solution;
[0094] Aluminum sulfate, triethanolamine and calcium acetate as coagulants are mixed, added into the wall material solution, stirred evenly, and spray-dried to obtain temperature-controlled release coagulant microcapsules;
[0095] Step 3, adding the water reducer into water, stirring at 300 rpm for 5 minutes with a magnetic stirrer until dissolved, then adding nanocellulose and nanosilicon dioxide, stirring at 1000 rpm for 15 minutes, and then ultrasonically treating for 30 minutes until uniform dispersion, to obtain a nanomaterial solution;
[0096] Step 4, the temperature controlled release coagulant microcapsules are mixed with the gelling agent nano calcium silicate, calcium sulfate whiskers and sodium sulfate, and stirred at a low speed of 300 rpm for 1 min until they are evenly dispersed, and then a film-forming agent, a thermal conductive agent, an anti-seepage agent, a suspending agent, a thickener, a defoaming agent and a preservative are added, and the mixture is stirred at a low speed for 2 min to obtain a powder material A;
[0097] Step 5: Slowly add the nano material solution into the powder material A and stir at a low speed for 2 minutes to obtain a new-old concrete interface adhesive.
[0098] Example 2
[0099] A new-old concrete interface adhesive comprises the following raw materials in parts by weight:
[0100]
[0101]
[0102] The coagulant is embedded in a wall material to form a controlled-release coagulant microcapsule, and is added in the form of a controlled-release coagulant microcapsule; the wall material of the controlled-release coagulant microcapsule, gelatin, will soften and dissolve at a temperature above 40 degrees Celsius, thereby releasing the coagulant;
[0103] The preparation method is the same as that of Example 1.
[0104] Example 3
[0105] A new-old concrete interface adhesive comprises the following raw materials in parts by weight:
[0106]
[0107]
[0108] The coagulant is embedded in a wall material to form a controlled-release coagulant microcapsule, and is added in the form of a controlled-release coagulant microcapsule; the wall material of the controlled-release coagulant microcapsule, gelatin, will soften and dissolve at a temperature above 40 degrees Celsius, thereby releasing the coagulant;
[0109] The preparation method is the same as that of Example 1.
[0110] Comparative Example 1
[0111] A new-old concrete interface binder, comprising the following raw materials in percentage: the same as Example 1, except that ordinary calcium silicate (particle size 50 μm) is used to replace the nano calcium silicate in Example 1, ordinary silicon dioxide (10 μm) is used to replace the nano silicon dioxide in Example 1, and ordinary cellulose (particle size 55 μm) is used to replace the nano cellulose in Example 1)
[0112] Comparative Example 2
[0113] A new-old concrete interface adhesive comprises the following raw materials in percentage: the same as Example 1, except that no thermal conductive agent is added.
[0114] The preparation method is the same as that of Example 1, except that no thermal conductive agent is added.
[0115] Comparative Example 3
[0116] A new-old concrete interface adhesive comprises the following raw materials in percentage: the same as Example 1, except that the coagulant is not embedded in the wall material gelatin but is directly added.
[0117] The preparation method thereof comprises the following steps:
[0118] Step 1, weigh each raw material according to proportion;
[0119] Step 2, adding the water reducer into water, stirring at 300 rpm for 5 minutes with a magnetic stirrer until dissolved, then adding nanocellulose and nanosilicon dioxide, stirring at 1000 rpm for 15 minutes, and then ultrasonically treating for 30 minutes until uniform dispersion, to obtain a nanomaterial solution;
[0120] Step 3, mixing the coagulant aluminum sulfate, triethanolamine, calcium acetate, nano calcium silicate, calcium sulfate whisker, and sodium sulfate, stirring at a low speed of 300 rpm for 1 min until uniformly dispersed, adding a film-forming agent, a thermal conductive agent, an anti-seepage agent, a suspending agent, a thickener, a defoaming agent, and a preservative, and continuing to stir at a low speed for 2 min to obtain a powder material A;
[0121] Step 4: Slowly add the nano material solution into the powder material A and stir at a low speed for 2 minutes to obtain a new-old concrete interface adhesive.
[0122] Effect example: Performance testing of adhesives and evaluation of operating window
[0123] 1. Test methods:
[0124] With reference to the standard "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GBT 50082-2009, laboratory methods were used to test the splitting tensile strength and impermeability and evaluate the operating window time of the binder. The results are shown in Table 1.
[0125] 1) Split tensile strength: Use a cubic test mold with a size of 150mm×150mm×150mm. First, pour half of the concrete in the test mold. After natural curing for 7 days, apply 0.5mm of adhesive. After curing for a certain period of time (1d, 3d, 7d, 14d), continue to pour concrete in the original test mold, smooth it, and test the splitting tensile strength after curing for 28d.
[0126] 2) Waterproof performance: A truncated cone with an upper inner diameter of 175 mm, a lower inner diameter of 185 mm and a height of 150 mm was used. A middle partition was placed in the mold, and concrete was poured on one side. After natural curing for 7 days, the adhesive was applied. After curing for several days (1d, 3d, 7d, 14d), concrete was poured on the other side. After curing for 28 days, the water-proof performance of the bonding surface was tested.
[0127] Trial Grouping
[0128] The new and old concrete interface adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were respectively tested according to the above method;
[0129] Test group 1: The new and old concrete interface adhesive prepared in Example 1 was used for testing;
[0130] Test group 2: The new and old concrete interface adhesive prepared in Example 2 was used for testing;
[0131] Test group 3: The new and old concrete interface adhesive prepared in Example 3 was used for testing;
[0132] Control group 1: The new and old concrete interface adhesive prepared in comparative example 1 was used for testing;
[0133] Control group 2: The new and old concrete interface adhesive prepared in comparative example 2 was used for testing;
[0134] Control group 3: The new and old concrete interface adhesive prepared in comparative example 3 was used for testing;
[0135] Control group 4: The commercially available cement-based penetrating crystalline waterproof coating was used as the adhesive at the interface between new and old concrete for the experiment;
[0136] Control group 5: During the test, no adhesive was applied to the interface between the new and old concrete. Instead, the new concrete was poured directly after the surface of the old concrete was cleaned.
[0137] Control group 6: whole concrete;
[0138] Comparison Group 7: The commercially available epoxy resin interface agent was used for the test (the test required that the other side of the concrete be poured immediately after the epoxy resin interface agent was applied)
[0139] 2. Results and Analysis
[0140] Table 1
[0141]
[0142] From the test results in Table 1, it can be seen that:
[0143] 1) In the test groups 1-3 of the present invention, the splitting tensile strength and impermeability at intervals of 1d, 3d, 7d and 14d were better than those of the control groups 1-3;
[0144] 2) The interface adhesive prepared in Examples 1-3 of the present invention can still obtain good splitting tensile strength (>0.9MPa) and interface impermeability (<5.7×10 -6 ), therefore, its operation window time>14d.
[0145] 3) When cement-based penetrating crystallization waterproof coating is used as the interface agent of construction joints, the performance weakens after 3 days. At an interval of 3 days, the splitting tensile strength is greater than that of the control group 5 without the interface agent, and the relative permeability coefficient is less than 5.7×10 -6 , therefore, its operation window is only 3 days.
[0146] In summary, the adhesive of the present invention has good splitting tensile strength, excellent impermeability and a long operating window period.
[0147] Effect Example 2: Engineering Verification
[0148] 1. Test methods
[0149] The adhesive prepared in Example 1 was used for concrete pouring construction, and the construction method was as follows:
[0150] Step A: Clean the surface of the old concrete to ensure that it is solid, clean, free of release agent, floating dust, floating slurry, oil stain, alkali, peeling, loose parts, and clear water; if the surface of the old concrete is too smooth, it needs to be roughened with adhesive;
[0151] Step B: Apply the adhesive at the interface between the new and old concrete on the surface of the old concrete in two even coats. After each coat, the surface should be protected. The amount of adhesive at the interface between the new and old concrete is 1.0kg / ㎡.
[0152] Step C: 7 days after the curing of the adhesive at the interface between the new and old concrete is completed, new concrete pouring construction is carried out to form a concrete side wall with a construction joint.
[0153] 2. Test indicators and results
[0154] The water leakage detection of the above-cast concrete side wall with construction joint is carried out according to the following method;
[0155] like Figure 1 As shown in the figure, the detection method of water leakage in construction joints is as follows:
[0156] (1) A waterproof layer is wrapped around the construction joint, a hollow water storage baffle is set on the surface of the waterproof layer, and grouting pipes and valves are pre-buried.
[0157] (2) The cavity water storage baffle is fixed to the outer waterproof layer with water-expanding waterproof glue and sealed on all sides.
[0158] (3) Pour the structural concrete and leave the grouting pipe end and valve inside the structural concrete;
[0159] (4) Water storage: When water is stored in the lower right grouting pipe and discharged from the upper left grouting pipe, or when water is injected from the lower left and discharged from the upper right, it means that the water storage area is full. Observations and records should be made every day during each water storage period, and the observation period should be no less than 15 days.
[0160] After testing and observation for 15 days, the above-mentioned poured concrete with construction joints showed no water leakage, and the overall impermeability of the construction joints was qualified.
[0161] The above-described embodiments are only preferred embodiments of the present invention, and are not exhaustive of the feasible implementations of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.
Claims
1. A new and old concrete interface adhesive, characterized in that: The following raw materials are included in parts by weight: The temperature-controlled-release coagulant microcapsules are core-wall structure coagulants that are formed by embedding the coagulant in a wall material.
2. The new-old concrete interface adhesive according to claim 1, characterized in that: The wall material includes one or more of gelatin, gum arabic, xanthan gum, polyvinyl alcohol, and polyacrylic acid; The coagulant includes one or more of aluminum sulfate, alcohol amine, and calcium salt; The alcohol amine includes one or more of diethanolamine and triethanolamine; The calcium salt includes one or more of calcium formate and calcium acetate.
3. The new-old concrete interface adhesive according to claim 2, characterized in that: The coagulant comprises 3-6 parts by weight of aluminum sulfate, 3-6 parts by weight of alcohol amine and 1-3 parts by weight of calcium salt.
4. The new-old concrete interface adhesive according to claim 2, characterized in that: The preparation method of temperature-controlled release coagulant microcapsules comprises the following steps: Add the wall material into the solvent and stir at 40-80 degrees Celsius until dissolved to prepare a wall material solution; The coagulant is added into the wall material solution, stirred evenly, and then spray-dried or concentrated and evaporated to dryness to obtain temperature-controlled release coagulant microcapsules.
5. The new-old concrete interface adhesive according to claim 1, characterized in that: The gelling agent includes one or more of nano calcium silicate, calcium sulfate whisker, sodium sulfate, and nano silicon dioxide; The film-forming agent includes one or more of redispersible polymer rubber powder, elastic emulsion, and styrene-acrylic emulsion; The crack inhibitor includes one or more of a nano-scale crack inhibitor and other crack inhibitors; The nano-scale crack inhibitor includes one or more of nano-plant fibers and nano-cellulose; Other crack inhibitors shown include carbon fiber; The thermal conductor is one or more of aluminum oxide, nano carbon black and graphite.
6. The new-old concrete interface adhesive according to claim 5, characterized in that: The gelling agent comprises 30-40 parts by weight of nano calcium silicate, 5-10 parts by weight of calcium sulfate whisker, 1-5 parts by weight of sodium sulfate and 1-10 parts by weight of nano silicon dioxide.
7. The new-old concrete interface adhesive according to claim 1, characterized in that: It also includes 0.05-0.1 parts by weight of a water reducing agent and / or 0.2-0.5 parts by weight of other additives; The other additives include water reducing agent, anti-seepage agent, suspending agent, thickening agent, defoaming agent and preservative.
8. The new-old concrete interface adhesive according to claim 1, characterized in that: The following raw materials are included in parts by weight: The coagulant is added in the form of temperature-controlled release coagulant microcapsules.
9. The new-to-old concrete interface adhesive according to any one of claims 1 to 8, characterized in that: It also includes water, and the amount of water used is 40-60% of the total weight of the powder material in the new and old concrete interface binder.
10. A method for preparing a new-old concrete interface adhesive, characterized in that: The steps include: Step 1, weighing each raw material in proportion, adding a water reducer into water, stirring and dissolving, adding the nano-silicon dioxide and nano-scale crack inhibitor in the gelling agent, stirring and dispersing and ultrasonically dispersing in turn to obtain a nano-material solution; Step 2: Mix the temperature-controlled release coagulant microcapsules and other materials in the gelling agent, stir and disperse them evenly, then add the film-forming agent, thermal conductive agent, other crack inhibitors and other additives, and continue stirring until they are evenly dispersed to obtain powder material A; Step 3: Add the nano material solution into the powder material A and stir until it is evenly dispersed to obtain the new and old concrete interface adhesive.
Citation Information
Cited By
Interface binder as well as preparation method and application thereof
CN120924207A